Science/technology/society projects for young scientists - Newton, David E. (New York : F. Watts, 1991)
Offers guidelines for a variety of experiments and projects related to science, technology, and society.
Includes bibliographical references and index.
School Library Journal.
Young Adult
Keywords: Engineering -- Experiments -- Juvenile literature; Engineering -- Social aspects -- Juvenile literature; Science -- Experiments -- Juvenile literature; Science -- Social aspects -- Juvenile literature; Engineering -- Experiments; Engineering -- Social aspects; Experiments; Science -- Experiments; Science -- Social aspects; Engineering -- Experiments; Engineering -- Social aspects; Science -- Experiments; Science -- Social aspects